Lattice dynamics, optical and thermal properties of quasi-two-dimensional anisotropic layered semimetal ZrTe2. Issue 16 (15th July 2021) - Muhammad, Zahir; Usman, Muhammad; Ullah, Sami; Zhang, Bo; Lu, Qixiao; Zhu, Ling; Hu, Rui
Abstract : In this study, an investigation was conducted on the vibrational properties exhibited by 2D layered zirconium ditelluride by employing Raman spectroscopy and confirmed by DFT calculation. Abstract : In this study, an investigation was conducted on the vibrational properties of 2D layered zirconium ditelluride by employing Raman spectroscopy. In addition, the surface electronic and optical properties of bulk ZrTe2 were studied by infrared spectroscopy. Two Raman-active modes were observed at 109.3 cm −1 (Eg ) and 145.2 cm −1 (A1g ) in ZrTe2, respectively, as compared with the DFT calculations. Next, the Raman modes were studied in depth from the bulk to bilayer over a range of temperatures. A1g and Eg soften with the increasing temperature from 80 to 300 K. Moreover, the softening of both vibrational modes was observed to show a strong association with the anharmonic interlayer phonon coupling or thermal expansion at different temperatures; hence, the phonon frequencies could be shifted. However, a blue shift was observed with the decrease in the number of layers, which are connected to the interlayer interaction, or the structural mismatch in layers compared with their bulk counterpart. Angle-resolved Raman spectroscopy revealed the anisotropic properties of ZrTe2 . Similarly, the optical properties exhibited by ZrTe2 suggested the co-existence of two types of charge carriers along with bound excitons in the infrared regime. Besides, the Hall measurements indicates the dominant electron-type carriers and high mobility at low temperatures in ZrTe2 . Furthermore, the calculated thermal conductivity of ∼5.4 W m −1 K −1 at ambient temperature showed ZrTe2 as a prominent candidate for thermoelectric devices. Accordingly, as revealed from the obtained results, ZrTe2 with different layers could be useful in spintronic and tunable thermoelectric devices.